“Propagación in vitro de piña (ananas comosus L merr), utilizando yemas axilares” - Delgado Haya, Henri (2004)
Our research had the following objectives: Developing a plant tissue culture media for in vitro differentiation of lateral buds in pineapple (Ananas comosus L. Merr.) obtained from field grown suckers, standardizing a optimal concentration of Benzilamino- purine (6-BAP) for in vitro shoot multiplication of pineapple and establishing a procedure for acclimatizing pineapple plantlets obtained in vitro. The culture media for differentiation was established after evaluation of lateral bud development using three treatments with Murashige & Skoog ( 1962) basal salts full strength. The best response differentiating lateral buds was obtained in a medium supplemented with Sucrose (30 g/I), 6-BAP (2mg/I) + Naftalene-acetic acid (ANA) 2mg/I and pH= 5.7. Our results suggest that optima! concentration for 6-BAP for shoot multiplication was 1.0 mg/I in a M&S basal SAL T culture medium. We have developed an efficient procedure for in vitro propagating and acclimatizing previously rooted pineapple (Ananas comosus L. Merr.) plantlets. lt will let us apply these techniques to mass propagation of new cultivars o "refreshing" the already used in San Martín.